The Influence of Work Flexibility and Compensation on Employee Performance among the Millennial Generation - Retno Anggraini; Habibullah Jimad; Nova Mardiana (Lembaga Pengembangan Kinerja Dosen, 2025)
The millennial generation that now dominates the world of work tends to prioritize work flexibility and compensation to improve their performance in the work environment. Work flexibility is considered as one of the important factors that can improve employee productivity and performance. Fair and competitive compensation is also a crucial aspect in motivating employees to achieve optimal performance. This study aims to determine the effect of work flexibility and compensation on the performance of millennial generation employees in insurance companies in Indonesia. This study is a quantitative study by distributing questionnaires using a Likert scale with a sample of 198 millennial generation employees in insurance companies spread throughout Indonesia. The data that has been collected will be analyzed using multiple linear regression analysis tools to test the influence between variables through the IBM SPSS 26 application. The results of this study support the proposed hypothesis, namely that work flexibility has a positive and significant effect on employee performance and compensation has a positive and significant effect on employee performance. The findings of this study provide implications for company management in designing work flexibility policies that provide freedom for employees to determine their start and finish hours, so that optimal employee welfare and performance are created.